2014
DOI: 10.1177/0022034514563335
|View full text |Cite
|
Sign up to set email alerts
|

PIN1 Inhibition Suppresses Osteoclast Differentiation and Inflammatory Responses

Abstract: Inflammatory responses and osteoclast differentiation play pivotal roles in the pathogenesis of osteolytic bone diseases such as periodontitis. Although overexpression or inhibition of peptidyl-prolyl cis/trans isomerase NIMA-interacting 1 (PIN1) offers a possible therapeutic strategy for chronic inflammatory diseases, the role of PIN1 in periodontal disease is unclear. The aim of the present study was to evaluate PIN1 expression in periodontitis patients as well as the effects of PIN1 inhibition by juglone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…Phosphorylation of many mitosis‐regulating proteases such as PLK‐11, Cdc25, and Cdc27 depends on Pin1 . Hence, modulation of Pin1 is reported in many processes and diseases ranging from inflammation and differentiation to vascular dysfunction and skin, breast, liver, and prostate cancers . In the present study therefore, we used juglone, an established Pin1 inhibitor, to check if it has any effect on an important process of wound healing in vitro and/or in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of many mitosis‐regulating proteases such as PLK‐11, Cdc25, and Cdc27 depends on Pin1 . Hence, modulation of Pin1 is reported in many processes and diseases ranging from inflammation and differentiation to vascular dysfunction and skin, breast, liver, and prostate cancers . In the present study therefore, we used juglone, an established Pin1 inhibitor, to check if it has any effect on an important process of wound healing in vitro and/or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Juglone, a natural compound found in walnuts, is a peptidyl‐prolyl cis/trans isomerase Protein Never in Mitosis Gene A Interacting‐1 (Pin1) inhibitor that was once assumed toxic to human cells . It is now known that juglone possesses anticancer, antiproliferative, antimicrobial, anti‐inflammatory, and anti‐aging capabilities . Walnuts have been used for hair dying and protecting against Alzheimer's disease and have been associated with anti‐inflammatory, anti‐oxidative, and antihemolytic activities .…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent of these is DC‐STAMP (dendritic cell‐specific transmembrane protein) (Kukita et al, 2004; Yagi et al, 2005; Iwasaki et al, 2008; Mensah et al, 2010; Chiu et al, 2012; Chiu and Ritchlin, 2016), which has been identified as one of the most essential single factors supporting both differentiation and fusion. However, also other factors such as CD47 (Han et al, 2000; Lundberg et al, 2007; Maile et al, 2011; Koskinen et al, 2013; Hobolt‐Pedersen et al, 2014), syncytin‐1 (Soe et al, 2011), OC‐STAMP (osteoclast stimulatory transmembrane protein) (Miyamoto et al, 2012; Witwicka et al, 2015), dynamin (Shin et al, 2014; Verma et al, 2014), Pin1 (peptidyl‐prolyl cis‐trans isomerase NIMA‐interacting 1) (Islam et al, 2014; Cho et al, 2015), and e‐cadherin (Mbalaviele et al, 1995; Fiorino and Harrison, 2016) are involved in OC fusion, but it is important to stress that this list is not exhaustive. In order to identify the role of these factors , a series of molecular techniques, and cellular model systems have been employed, which in general are evaluated through end‐point measurements by counting the number of multi‐nucleated OCs, number of nuclei per OC, resorptive activity, and so forth at the end of the incubation period.…”
mentioning
confidence: 99%
“…PDL cells treated with both nicotine and LPS are an in vitro model used to recapitulate the effects of periodontitis in smokers with poor oral hygiene 8 . The combination of nicotine and LPS stimulates the formation of osteoclast‐like cells by increasing macrophage colony‐stimulating factor (M‐CSF) and PGE 2 production in osteoblasts 9 and increases PGE 2 and cyclooxygenase‐2 (COX‐2) expression in osteoblasts 10 .…”
mentioning
confidence: 99%